THE EFFECT OF ATTENTIONAL INTERFERENCE ON A ROCK CLIMBING TASK: A PILOT STUDY - Patrick R. Young (Pamukkale University, 2012)
Preparatory behavior has been identified as being beneficial (i.e., achieving optimal emotional states, focused attention, etc.) to performance within various sport domains. Participants of risk sport (i.e., rock climbing, surfing, skydiving, among others) have been reported to engage in this behavior (i.e., preparatory routines, plans, strategies, etc.) in an attempt to reduce the degree of uncertainty within their domains. The ability to employ this type of behavior however requires cognitive resources and attentional focus. The present pilot study examined the effect of decreased cognitive resources (i.e., through interference tasks)on performance in a risk sport activity (i.e., rock climbing). Rock climbers (N = 18), whose attentional focus was manipulated through a series of resource-depleting tasks, climbed significantly slower,t (16) = -2.34, p< .03, than climbers who were uninhibited. The necessity of cognitive resources in preparing for a risk sport task and how the depletion of such resources may impair performance in such a task isdiscussed.